Pesantren Salaf dan Perubahan Sosial (Studi Kasus Pesantren Salaf Al Anwar Sarang Rembang) - Murtadlo Murtadlo (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractGlobalization and modernization of information sponsored by the state have resulted in a variety of social changes. The impact on social changes must be faced by all social institutions, including traditional Islamic boarding school (or called pesantren salafiyah in Indonesia). One important issue in dealing with challenges of social changes is the identity issue. How is traditional Islamic boarding school identity in dealing with social changes? This study attempts to analyze the model of traditional Islamic boarding school identity creation in dealing with social changes. The study took the case of Al-Anwar Traditional Islamic boarding school, Sarang, Rembang in Central Java. The study found that the traditional Islamic boarding school has developed a specific identity creation in dealing with social changes.AbstrakGlobalisasi informasi dan modernisasi yang disponsori oleh negara telah menghasilkan berbagai perubahan sosial. Dampak perubahan sosial ini harus dihadapi oleh semua institusi sosial, termasuk Pesantren salaf. Salah satu isu penting dalam menghadapi tantangan perubahan sosial adalah masalah identitas. Bagaimana identitas pesantren salaf menghadapi perubahan sosial tersebut? Studi ini mencoba mengkaji model kreasi identitas pesantren salaf menghadapi perubahan sosial. Studi mengambil kasus pada Pesantren Salaf Al Anwar Sarang Rembang Jawa Tengah. Studi ini menemukan bahwa pesantren salaf dalam mengahadapi perubahan sosial telah mengembangkan kreasi identitas tertentu.